1985
DOI: 10.1177/019262338501300411
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Histologic Distribution of Rat Bone Marrow Cells with Respect to Age and Anatomic Site

Abstract: Bone marrow cellularity in untreated Fischer 344/N rats was subjectively evaluated in hematoxylin and eosin (H & E)-stained histologic sections from femur, tibia, humerus, sternum, lumbar vertebrae, ribs, pelvis, and skull of 2-, 4-, 7-, 16-, and 24-month-old males. Marrow cellularity varied with age of the rat and bone site sampled. Hematopoietic cellularity was consistently higher in rats less than 4 months of age and less consistently higher in 24-month-old rats versus intermediate age groups examined. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
1
25
0
2
Order By: Relevance
“…In fact, undernutrition during the rapid growth stage is thought to cause changes, such as hemocytopenia, that are nearly equal to those induced by immunotoxicants. Many reports concerning hematological changes in dietary restricted rats 4–9 or nontreated rats with age-related physiological data 10–13 have been published. However, few reports have examined age-related hematological changes in dietary restricted rats.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, undernutrition during the rapid growth stage is thought to cause changes, such as hemocytopenia, that are nearly equal to those induced by immunotoxicants. Many reports concerning hematological changes in dietary restricted rats 4–9 or nontreated rats with age-related physiological data 10–13 have been published. However, few reports have examined age-related hematological changes in dietary restricted rats.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows the segmented results of the rat skeletal system, mineral bone, RBM, and YBM. The cellularity of different bones is presented in Table II along with those reported by Cline et al 32 Supplemental Tables 1 and 2 ͑Ref. 57͒ show the AF results for the mineral bone ͑including cortical bone and trabecular bone͒, the RBM, and the YBM in the 40 defined bone sites, calculated for photon and electron sources placed in 18 source organs and seven bone locations.…”
Section: Resultsmentioning
confidence: 99%
“…34 Generally, the youngest rats have the highest marrow cellularity. Cline et al 32 reported that, regardless of the site, the mean marrow cellularity was 80% at 2 months of age; by 2 yr of age, the cellularity decreased to a mean of 66%. Table II shows marrow cellularities of the rat phantom at 11 bone sites.…”
Section: Iva the Mass Of Updated Organs And Skeletal Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…For small laboratory animal species (e.g., rat, mouse, guinea pig), samples of bone marrow for histological examination may be acquired from any one of several bones with hematopoietically active marrow (e.g., sternum, rib, humerus, and femur). Regardless of age, the distal tibia of the rat has a demonstrable lack of active hematopoiesis, suggesting that this site is unacceptable for histological bone marrow evaluations (Cline and Maronpot 1985). The sternum and distal femur are sites that have been routinely used for bone marrow histology in small laboratory animals.…”
Section: Bone Marrow Collection and Processingmentioning
confidence: 99%